MOTIVATION OF WOMEN ENTREPRENEURS: EVIDENCE FROM MSMEs IN RIAU ISLANDS PROVINCE - Muhammad Rizki; Anoesyirwan Moeins; Marhalinda (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
Most women entrepreneurs in Indonesia are engaged in Micro, Small, and Medium Enterprises (MSMEs).In Riau Islands Province, the number of women entrepreneurs in the MSMEs field is consistently larger than male entrepreneurs in the period of 2017-2019. With the rising numbers of women entrepreneurs in Riau Islands Province and their increasing dominance in the MSMEs sector, this study aims to explore the motivational factors of women entrepreneurs in the MSMEs sector in Riau Islands. This research adopted a qualitative approach and used qualitative interviews as data collection method. A total of 15 women entrepreneurs from Tanjungpinang City, the capital of Riau Islands Province, were chosen as participants in this study. The data gathered were analyzed using thematic analysis with the help of NVIVO software. The result of this study shows that financial rewards, social support, personal satisfaction, external opportunities, and independence are the factors that motivate women to become entrepreneurs